Application of vascular ports at patients treated with chemotherapy - Piątek, Kamila; Karczmarek-Borowska, Bożenna (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Treatment with chemotherapy is related to local reactions as results of accidental extravasation of drug. It is estimated that about 0,45-6,4 percent of patients suffer from extravasation of cytostatic drugs to perivascular space during chemotherapy. In case of the patients who are going to take chemotherapy, especially long term chemotherapy, it is suggested implantation of vascular port in order to give cytostatic drugs, infusions, whole blood or blood products. The mentioned system prevents local side-effects of extravasation of drugs. Vascular port guarantees permanent intravenous access. It is necessary to use in treatment of colorectal cancer, breast cancer and lymphoma. It is also used in treatment of the patients with some chronic disease, with being in terminal care and children with haemophilia. Contradictions to implantation are the same as in case of each vascular access system and they include coagulation disorders, infections and dermatosis in the place of planned operation. After implanting of the port, there might appear complications such as pneumothorax, blood-vessel perforation or heamatoma in the place of implantation of the port. Late complications comprise thrombosis and local or general infections. Occasionally dermatonecrosis, catheter migration and occlusion appear. The patients with the port should limit physical activity involving arms and schoulder girdle. They schould not press the place near the catheter, so as not to disturb the work of the port. When catheter is not used for four weeks, it is required to fill it with heparin solution. Vascular ports at patients treated with chemotherapy improve their quality of life.